2015
DOI: 10.1590/2317-1782/20152014162
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial functions and quality of life in oral health in subjects with dentofacial deformity

Abstract: The facial pattern influenced the performance of the OFFs and the QoL in individuals presenting DFD, with a greater occurrence of changes for patterns II and III, and the worse the OFFs, the worse the QoL in cases with DFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
2
12
0
7
Order By: Relevance
“…Among stomatognathic functions, only mastication presented one variable associated with MB diagnosis, that is, the presence of unexpected contraction of orbicularis and mentalis muscles during mastication with a 2.97-times greater probability for this outcome. As mentioned above, chronic unilateral masticatory pattern and excessive contraction of mentalis and perioral musculature during mastication were related to convex facial type, an MB characteristic also found in the present study (26) . During mastication, unsystematic lip sealing, tongue interposition and tension in mentalis and orbicularis oris muscles, necessary to keep food inside the mouth for swallowing, were also observed in the MB child group (27) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Among stomatognathic functions, only mastication presented one variable associated with MB diagnosis, that is, the presence of unexpected contraction of orbicularis and mentalis muscles during mastication with a 2.97-times greater probability for this outcome. As mentioned above, chronic unilateral masticatory pattern and excessive contraction of mentalis and perioral musculature during mastication were related to convex facial type, an MB characteristic also found in the present study (26) . During mastication, unsystematic lip sealing, tongue interposition and tension in mentalis and orbicularis oris muscles, necessary to keep food inside the mouth for swallowing, were also observed in the MB child group (27) .…”
Section: Discussionsupporting
confidence: 88%
“…A cephalometric study found no difference between mouth and nasal breathing children in nasolabial angle, however convex facial type and diagnosis for MB were associated (8) . Convex facial type was associated with mouth and mist breathing mode, chronic unilateral masticatory pattern, excessive contraction of mentalis and perioral musculature during mastication and forward tongue and head movement during swallowing (26) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the subjects of this study showed low values of pressure of the lips, corroborating with other studies that evaluated the said structure under other conditions [21][22][23][24][25] . Improper pressure peak of Class I subjects may be explained by the fact of not having been considered, differences in the facial profile of the subjects (dolichofacial, mesofacial and brachyfacial), whereas, in the vertical plane, literature also reports muscular pattern modification in structure function 6 . In addition, the population of subjects without change, studied for the reference values of IOPI, is of American nationality 16 , which could have differed from subjects of this research due to ethnic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with maxillomandibular disproportions have myofunctional and facial profile characteristics according to the type of disproportion of that feature. Muscle adaptations that occur in various types of dentofacial deformities (DFD) enable the realization of stomatognathic functions that are performed according to the pattern of the maxillofacial skeleton bone structure 6 .…”
Section: Introductionmentioning
confidence: 99%